Protective Effects of the Soluble Epoxide Hydrolase Inhibitor 1-Trifluoromethoxyphenyl-3-(1-Propionylpiperidin-4-yl) Urea in a Rat Model of Permanent Middle Cerebral Artery Occlusion - Zhang, Linlei; Xu, Shasha; Wu, Xiaoxiao; Muse, Farah Mohamed; Chen, Jiaou; Cao, Yungang; Yan, Jueyue; Cheng, Zicheng; Yi, Xingyang; Han, Zhao (Frontiers in Pharmacology, 2020)
Acute ischemic stroke is a serious disease that endangers human health. In our efforts to develop an effective therapy, we previously showed that the potent, highly selective inhibitor of soluble epoxide hydrolase called 1-trifuoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea (TPPU) protects the brain against focal ischemia in rats. Here we explored the mechanism of TPPU action by assessing whether it could preserve blood-brain barrier integrity and reduce apoptosis in the brain during permanent middle cerebral artery occlusion in male Sprague-Dawley rats. TPPU administration at the onset of stroke and once daily thereafter led to smaller infarct volume and brain edema as well as milder neurological deficits. TPPU significantly inhibited the activity of soluble epoxide hydrolase and matrix metalloproteases 2 and 9, reducing 14,15-DHET levels, while increasing expression of tight junction proteins. TPPU decreased numbers of apoptotic cells by down-regulating the pro-apoptotic proteins BAX and Caspase-3, while up-regulating the anti-apoptotic protein BCL-2. Our results suggest that TPPU can protect the blood-brain barrier and reduce the apoptosis of brain tissue caused by ischemia.